Normative framework of Catholic institutions of higher education - Orrego, Cristóbal (Church, Communication and Culture, 2024)
Catholic institutions of higher education are in the world with a purpose that stems from an identity rooted in the life and the faith of the Church. Their reality is partially constituted and guided by a set of principles and rules of law. This ‘normative framework’ defines the path of each university toward the common good. Norms are also essential for stabilizing the life of these organizations and for protecting their identity and mission throughout time. This article presents a summary of that normative framework, to furnish a specific perspective—the legal point of view—for observing, understanding, and assessing the reality of these institutions. The article starts with a reflection on general issues that foster such an understanding and then proceeds to present the principles and norms that constitute such normative framework: natural and divine positive law, public international law and state law, and, finally, the basic norms of Church law: the Code of Canon Law (1983), the Code of the Canons of Eastern Churches (1990), and the Apostolic Constitutions Ex Corde Ecclesiae (1990) and Veritatis Gaudium (2017), with some reference to its predecessor Sapientia Christiana (1979).